Depo Medroxyprogesterone Acetate Injection was Associated with a Greater Risk of Diabetes Mellitus: a Study at East Jakarta Public Health Centres - Bonaville, Edwin (Indonesian Journal of Obstetrics and Gynecology, 2012)
Objective: To study the relationship between the history of contraceptive injection depo medroxyprogesterone acetate (DMPA) exposure with incidence of diabetes mellitus and the associated risk factors. Methods: This is a case-control study conducted in 6 Public Health Centers in East Jakarta involving 30 cases of diabetes mellitus and 61 controls. Body mass index (BMI), parity, type of contraception, duration of contraceptive use, history of gestational diabetes and breastfeeding were assessed in each group. Data were analyzed with Chi Square or Fisher’s test, and logistic regression. Results: The mean age of the subjects was 45.00 (35-67) years, with a median number of parity of 3.00 (0-7), and the median of BMI was 27.31 (15.24 to 40.27). The number of DMPA injections users was 31.9% and the mean duration of contraception usage was 5.36 ± 4.42 years. There was a correlation between the history of DMPA injections with incidence of diabetes mellitus, with an odds ratio of 3.36 95% CI [1.098 to 10.469]. The risk persisted after adjustment of age and BMI. Conclusion: DMPA exposure was associated with a greater risk of diabetes mellitus. Risk was associated with length of use and persisted after adjusment with age and BMI. [Indones J Obstet Gynecol 2012; 36-2: 100-4 Keywords: depo medroxyprogesterone acetate (DMPA), diabetes mellitus